Proceedings of the 6th Annual Conference on the Teaching of Computing and the 3rd Annual Conference on Integrating Technology I 1998
DOI: 10.1145/282991.283046
|View full text |Cite
|
Sign up to set email alerts
|

Using the personal software process to motivate good programming practices

Abstract: A reduced form of the Personal Software Process was used in two introductory programming courses to help students learn the value of a proper programming methodology. Students collected data during the development of their programming projects and that data was summarised and presented to the class as a whole. From the data, students were able to conclude on their own the value of early software development stages (planning, design and review) in reducing debugging time and in producing better quality software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Some qualitative analyses have shown that undergraduate students in PSP courses were concerned more with programming than with software process issues and that they were not ready to appreciate the benefits of addressing those issues [13][14][15]. In these works, the students were applying PSP in introductory programming courses during their first year of university studies.…”
Section: Design Experimentalmentioning
confidence: 99%
“…Some qualitative analyses have shown that undergraduate students in PSP courses were concerned more with programming than with software process issues and that they were not ready to appreciate the benefits of addressing those issues [13][14][15]. In these works, the students were applying PSP in introductory programming courses during their first year of university studies.…”
Section: Design Experimentalmentioning
confidence: 99%
“…Existen iniciativas satisfactorias en el plano académico, con sus respectivos métodos, para enseñar un proceso de software en cursos básicos utilizando el PSP [37], en que se reconoce lo prematuro que es en estos casos introducir completamente sus conceptos [8,19,26]. También se pueden encontrar experiencias positivas aplicando PSP, aunque con algunas adaptaciones, en otros cursos como por ejemplo, introducción a base de datos [34].…”
Section: Herramientas De Apoyo Para La Implementación De Pspunclassified
“…We have already found several reports of lectures using the PSP [6,7,12,11,14], and most lectures use the subset of the PSP. The reason is that there is not enough time and effort in such lectures.…”
Section: Discussionmentioning
confidence: 99%
“…Software process improvement is achieved by evaluating the data with respect to several metrics. The evaluation of the PSP also contributes for students to know the benefits of particular methods [6,12].…”
Section: The Pspmentioning
confidence: 99%